Intensity-modulated radiation therapy (IMRT) with different combinations of treatment-planning systems and linacs: issues and how to detect them - Dobler, Barbara; Lorenz, Friedlieb; Wertz, Hansjörg; Polednik, Martin; Wolff, Dirk; Steil, Volker; Lohr, Frank; Wenz, Frederik (Strahlentherapie und Onkologie, 2006)
Purpose: To compare different combinations of intensity-modulated radiation therapy (IMRT) system components with regard to quality assurance (QA), especially robustness against malfunctions and dosimetry. Material and Methods: Three different treatment-planning systems (TPS), two types of linacs and three multileaf collimator (MLC) types were compared: commissioning procedures were performed for the combination of the TPS Corvus (R) 5.0 (Nomos) and KonRad (R) v2.1.3 (Siemens OCS) with the Linacs KD2 (R) (Siemens) and Synergy (R) (Elekta). For PrecisePLAN (R) 2.03 (Elekta) measurements were performed for Elekta Synergy only. As record and verify (R&V) system Multi-Access v7 (R) (IMPAC) was used. The use of the serial tomotherapy system Peacock (R) (Nomos) was investigated in combination with the Siemens KD2 Linac. Results: In the comparison of calculated to measured dose, problems were encountered for the combination of KonRad and Elekta MLC as well as for the Peacock system. Multi-Access failed to assign the collimator angle correctly for plans with multiple collimator angles per beam. Communication problems of Multi-Access with both Linacs were observed, resulting in incorrect recording of the treatment. All reported issues were addressed by the manufacturers. Conclusion: For the commissioning of IMRT systems, the whole chain from the TPS to the Linac has to be investigated. Components that passed the commissioning in another clinical environment can have severe malfunctions when used in a new environment. Therefore, not only single components but the whole chain from planning to delivery has to be evaluated in commissioning and checked regularly for QA.